The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jcmg.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

CMR Guidance for Recanalization of Coronary Chronic Total Occlusion

Abstract: In this small group of patients showing CMR evidence of significant myocardial inducible perfusion defect and viability, CTO recanalization reduces ischemic burden, favors reverse remodeling, and ameliorates quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 24 publications
4
43
1
1
Order By: Relevance
“…All three mentioned studies [911] showed that the improvement in regional wall thickening after a successful CTO-PCI was indirectly related to the transmurality of LGE in a myocardial segment. More recently and in consonance with our findings, Bucciarelli-Ducci et al [12] reported a significant improvement in LVESV and LVEF after successful CTO-PCI in a group of 32 patients with preserved LVEF showing CMR evidence of myocardial viability and ischemia. Other than older studies assessing LVEF with contrast ventriculography [13, 14], Valenti et al published the only large study to date showing improved LVEF after successful CTO recanalization [15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All three mentioned studies [911] showed that the improvement in regional wall thickening after a successful CTO-PCI was indirectly related to the transmurality of LGE in a myocardial segment. More recently and in consonance with our findings, Bucciarelli-Ducci et al [12] reported a significant improvement in LVESV and LVEF after successful CTO-PCI in a group of 32 patients with preserved LVEF showing CMR evidence of myocardial viability and ischemia. Other than older studies assessing LVEF with contrast ventriculography [13, 14], Valenti et al published the only large study to date showing improved LVEF after successful CTO recanalization [15].…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of patients with history of previous myocardial infarction and the high prevalence of classic cardiovascular risk factors in this cohort are consistent with previous published data [22, 23]. Improvement in angina status after CTO-PCI has also been shown in previous studies in patients with preserved LVEF [7, 8, 12, 16, 18]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thirty‐four observational studies [including two abstracts ] with a total of 2804 patients met our inclusion criteria . Cardiac magnetic resonance imaging (CMR) was used to assess LVEF in nine studies while echocardiography was used in 10 studies . Other studies used left ventriculography or nuclear imaging, or did not specify the method used for assessing LVEF .…”
Section: Resultsmentioning
confidence: 99%
“…Regional myocardial function, measured as segmental wall thickening (SWT), improved in segments with a transmural extent of infarction (TEI) of <75%, and was unchanged in patients with TEI ≥75%. A study of 50 consecutive patients with a CTO who underwent contrast enhanced CMR showed that 32 patients (64%) had inducible ischemia and myocardial viability within the CTO territory (12). These 32 patients underwent a second CMR at 3 months after CTO PCI.…”
mentioning
confidence: 99%